Multiproxy reconstruction of oceanographic conditions in the southern epeiric Kupferschiefer Sea (Late Permian) based on redox-sensitive trace elements, molybdenum isotopes and biomarkers - Ruebsam, W.; Dickson, A.; Hoyer, E.; Schwark, Lorenz (Elsevier BV, 2017)
The key drivers controlling the redox state of seawater and sediment pore waters in low energy environments can be inferred from redox-sensitive trace elements (RSTE), molecular biomarkers and trace metal isotopes. Here, we apply a combination of these tools to the Upper Permian Kupferschiefer (T1) from the Thuringian Basin, deposited in the southern part of the semi-enclosed Kupferschiefer Sea. Enrichment patterns of the RSTEs molybdenum (Mo) and uranium (U) as well as biomarker data attest to the rapid development of euxinic conditions in basin settings during early T1 times, which became progressively less extreme during T1 deposition. The evolution of redox conditions in basinal settings, and the associated delay in the onset of euxinia at more shallow marginal sites, can be attributed to the interaction of sea-level change with basin paleogeography. Euxinia in the southern Kupferschiefer Sea did not lead to near-quantitative depletion of aqueous Mo, possibly due to short deepwater renewal times in the Thuringian Basin, low aqueous H2S concentrations, the continuous resupply of RSTE during transgression and declining burial rates of RSTEs throughout T1 times. Drawdown of RSTE is, however, indicated for euxinic lagoon environments. Moreover, admixture of freshwater supplied to these lagoons by rivers strongly impacted local seawater chemistry. The highest Mo-isotope compositions of ~ 1.70‰ in basin sediments allow a minimum Kupferschiefer Sea seawater composition of ~ 2.40‰ to be estimated. This composition is similar to the ~ 2.30‰ estimate for the Late Permian open ocean, and confirms a strong hydrographic connection between the epeiric Kupferschiefer Sea and the global ocean. The substantial variation in Mo-isotope signatures is paralleled by diagnostic shifts in biomarkers responding to oxygenation in different parts of the water column. Water column chemistry has been affected by variation in sea level, hydrodynamic restriction, riverine freshwater influx and evaporitic conditions in shallow lagoons. Elucidation of the relative role of each driving factor by a single geochemical proxy is not feasible but the complex scenario can be disentangled by a multiproxy approach.